The Implementation of the Make A Match Type Cooperative Learning Model in Social Science Subjects to Improve the Learning Outcomes of Fourth Grade Students at Manuwui Public Elementary School - Teky, Rahel; Ritiauw, Samuel Patra; Rumtutuly, Fransheine (Honoli of Journal Primary Teacher Education, 2025)
The purpose of this study is to determine the learning outcomes in Social Science through the implementation of the Make-A-Match type cooperative learning model in Grade IV at Manuwui Public Elementary School. The research method used is Classroom Action Research (CAR). The subjects of this study were 12 fourth-grade students of Manuwui Public Elementary School, consisting of 4 boys and 8 girls. The initial test results showed that the average classical mastery score of the students was 47.5, with only 2 students (17%) meeting the minimum mastery criteria (MMC). An improvement was observed in Cycle I, where 8 students (66.66%) achieved scores that met the MMC of 65, with an overall average score of 62.5. Student learning outcomes continued to improve in Cycle II. All 12 students (100%) met the MMC, and the overall average score in the final test of the second meeting in Cycle II increased to 77.5. This improvement was driven by the implementation of an engaging and participatory learning model, as well as improvements in teaching strategies based on reflections from the previous cycle.